2019
DOI: 10.1371/journal.pone.0215635
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of continuum of care for maternal, newborn, and child health services in rural Khammouane, Lao PDR

Abstract: Introduction The concept of continuum of care has gained attention as measures to improve maternal, newborn, and child health. However, little is known about the factors associated with the coverage level of continuum of care in Lao PDR. Therefore, this study was conducted 1) to investigate the coverage level of continuum of care and 2) to identify barriers and promoting factors that are associated with mothers’ continuation in receiving services in rural Lao PDR. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
83
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 20 publications
23
83
6
1
Order By: Relevance
“…The analysis shows that women who have husbands/partners are more likely to use ANC. This is in line with the findings of several studies that have shown the role of a husband/partner in providing support for a woman's healthy lifestyle [32][33][34][35]. Some other studies actually encourage a husband to help improve a woman's health status by actively encouraging a healthier lifestyle [36,37].…”
Section: Discussionsupporting
confidence: 88%
“…The analysis shows that women who have husbands/partners are more likely to use ANC. This is in line with the findings of several studies that have shown the role of a husband/partner in providing support for a woman's healthy lifestyle [32][33][34][35]. Some other studies actually encourage a husband to help improve a woman's health status by actively encouraging a healthier lifestyle [36,37].…”
Section: Discussionsupporting
confidence: 88%
“…Logistical barriers such as distance to facilities and time were rarely mentioned as obstacles in assuring biomedical treatment. However, many studies conducted in LMICs recognize geographic accessibility as a significant impediment to achieving care, particularly in rural settings [32][33][34]. This contrast may have been because study participants were recruited from the catchment area of local health centers and thus, participants may not have been likely to reside in hyper-rural areas far from health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated socio-economic inequalities and found socioeconomic determinants of prenatal and postnatal visits [17][18][19], explored influence of health policy on improving the utilisation of hospital delivery [20], prenatal or postnatal visits [21], fewer studies explore the utilisation of CMHS. To date, there has been some research exploring the determinants, effects, value, measurement of CMHS in LMICs outside of China: in Lao PDR [22], Nepal [23], Tanzania [10], South Africa [11], Cambodia [24].…”
Section: Introductionmentioning
confidence: 99%